2010
DOI: 10.1007/s12011-010-8847-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Parathyroid Hormone Levels in Chronic Endemic Fluorosis

Abstract: Endemic waterborne fluorosis is a public health problem in Isparta, a city located in southern Turkey. Fluoride is a cumulative element that increases metabolic turnover of the bone and also affects the homeostasis of bone mineral metabolism. There are number of similarities between the effects of excess parathyroid hormone (PTH) and fluorosis on bone. So fluoride might show its effect via PTH. We aimed to determine PTH levels in patients with endemic fluorosis to estimate the possible toxic effects of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…It has also been reported that chronic exposure to F may disturb Ca homeostasis by producing hypocalcaemia due to its stimulating effect on osteoblastic cell proliferation ( 10 12 ) , resulting in an increase in bone formation ( 13 15 ) , which needs extra Ca. This alteration of extracellular Ca level is sensed by Ca-sensing receptor (CASR) ( 16 ) and the parathyroid glands are triggered to secrete more parathyroid hormone to combat the Ca imbalance in the body, producing secondary hyperparathyroidism ( 14 , 17 ) . Parathyroid hormone triggers the conversion of 25-hydroxy-vitamin D 3 (25(OH) vitamin D 3 ) to 1,25-dihydroxy-vitamin D 3 (1,25(OH) 2 vitamin D 3 ) in the proximal convoluted tubule of the kidneys ( 18 ) to maintain plasma ionised Ca concentrations within narrow physiological limits by acting on the intestine, kidneys and bone ( 18 ) through its receptor – vitamin D receptor (VDR) ( 19 ) .…”
mentioning
confidence: 99%
“…It has also been reported that chronic exposure to F may disturb Ca homeostasis by producing hypocalcaemia due to its stimulating effect on osteoblastic cell proliferation ( 10 12 ) , resulting in an increase in bone formation ( 13 15 ) , which needs extra Ca. This alteration of extracellular Ca level is sensed by Ca-sensing receptor (CASR) ( 16 ) and the parathyroid glands are triggered to secrete more parathyroid hormone to combat the Ca imbalance in the body, producing secondary hyperparathyroidism ( 14 , 17 ) . Parathyroid hormone triggers the conversion of 25-hydroxy-vitamin D 3 (25(OH) vitamin D 3 ) to 1,25-dihydroxy-vitamin D 3 (1,25(OH) 2 vitamin D 3 ) in the proximal convoluted tubule of the kidneys ( 18 ) to maintain plasma ionised Ca concentrations within narrow physiological limits by acting on the intestine, kidneys and bone ( 18 ) through its receptor – vitamin D receptor (VDR) ( 19 ) .…”
mentioning
confidence: 99%
“…Osteosclerosis on imaging and bone biopsy are consistent with the disease. Secondary hyperparathyroidism is also frequently noted [3,4]. While elevated serum, urine, and bone fluoride levels are usually seen, urinary fluoride levels can remain elevated despite normal serum levels following cessation of inhalant abuse, as occurred in our case (the patient had refrained for two months prior to presentation due to psychiatric hospitalization) [5][6][7].…”
Section: Discussionmentioning
confidence: 50%
“…Although, clinical cases of skeletal fluorosis are rare in the United States [Kurland et al, 2007; Whyte et al, 2008] in other parts of the world where skeletal fluorosis is more common, patients often demonstrate pseudo-hyperparathyroidism [Teotia and Teotia, 1973; Teotia et al, 1998; Gupta et al, 2001; Xu et al, 2010; Koroglu et al, 2011]. Epidemiologic studies show that individuals of the population exposed to similar fluoride levels demonstrate variable skeletal features ranging from excessive bone formation to bone resorption [Teotia et al, 1998; Harinarayan et al, 2006].…”
Section: Discussionmentioning
confidence: 99%